The Prevalence and Clinical Significance of Anaerobic Bacteria in Major Liver Resection - Jens Strohäker; Sophia Bareiß; Silvio Nadalin; Alfred Königsrainer; Ruth Ladurner; Anke Meier (MDPI AG, 2021)
(1) Background: Anaerobic infections in hepatobiliary surgery have rarely been addressed. Whereas infectious complications during the perioperative phase of liver resections are common, there are very limited data on the prevalence and clinical role of anaerobes in this context. Given the risk of contaminated bile in liver resections, the goal of our study was to investigate the prevalence and outcome of anaerobic infections in major hepatectomies. (2) Methods: We retrospectively analyzed the charts of 245 consecutive major hepatectomies that were performed at the department of General, Visceral, and Transplantation Surgery of the University Hospital of Tuebingen between July 2017 and August 2020. All microbiological cultures were screened for the prevalence of anaerobic bacteria and the patients' clinical characteristics and outcomes were evaluated. (3) Results: Of the 245 patients, 13 patients suffered from anaerobic infections. Seven had positive cultures from the biliary tract during the primary procedure, while six had positive culture results from samples obtained during the management of complications. Risk factors for anaerobic infections were preoperative biliary stenting (p = 0.002) and bile leaks (p = 0.009). All of these infections had to be treated by intervention and adjunct antibiotic treatment with broad spectrum antibiotics. (4) Conclusions: Anaerobic infections are rare in liver resections. Certain risk factors trigger the antibiotic coverage of anaerobes.